The Influence of Nanofilled Polymer Coatings and Magnetic Field on the Decay Kinetics of Photovoltage in Silicon Crystals Used in Solar Energy - Steblenko, L P; Korotchenkov, O A; Podolyan, A A; Yashchenko, L M; Kalinichenko, D V; Kuryliuk, A N; Kobzar, Yu L; Gorbatenko, A N; Krit, A N; Naumenko, S N (Journal of Nano- and Electronic Physics, 2015)
The influence of a weak stationary magnetic field on the kinetics of photovoltage decay in "solar" silicon crystals (solar-Si) with nanofilled polymer coatings is studied. The characteristic features of magnetostimulated change of carrier lifetime depending on the concentration and the method of forming the nanofillers in the polymer matrix are established.